Vibrational frequencies and modes of a kinked inflatable beam. (October 2022) - Guo, Jiaming; Zhang, Zaoxu; Wang, Changguo
Abstract: Inflated beams are under increasing application in various structures. Many inflatable structures have kinks during use due to folding or initial material defects. A specific emphasis is often placed on determining the static characteristics of inflated beams in bending and wrinkling. From the perspective of mobility, a kink is needed to realize the movement of the structure, namely the vibration-containing kink. There is a lack of knowledge in dynamic conditions, especially for simple and accurate solutions for kinked inflatable beams. This paper studies the vibrational frequencies and modes of kinked inflatable beams and deals with the theoretical analysis of the natural frequencies of kinked inflatable beams. The first-order natural frequency of the kinked inflatable beam is predicted by introducing the kink parameters, and the inflated pressure into the vibration equation of the beam. The predictions on the natural frequency agree well with the vibration test. Results reveal that the kink decreases the first-order natural frequency of the inflated beam greatly, and the beam has no global vibration mode but only a higher mode. The present results can provide meaningful guidance for innovative inflated structure design.